Investigation to various parameters of a multi-layered one port surface acoustic wave resonator. (2022) - Turuk, Baruna Kumar; Behera, Basudeba
Abstract: This work presents the finite element simulation and analysis of various parameters of a hetero structure one port surface acoustic wave (SAW) resonator. The SAW resonator is made of two-layer structure composed of lithium Niobate (LN) and Diamond. In this study, we investigated the two-layer structure, in which the silicon dioxide layer is removed from a three layered structure and found a high-quality factor in result. In response to the increased mobile data traffic there is a growing need for more low loss radio band filters and a high-quality factor resonator, frequency, and velocity is required to achieve. We studied numerical analysis using a finite element method indicated that the acoustic wave energy can be lies near the surface of the structure of the surface in the two layer devices. It observed that two-layer structured quality factor more than three layers structured. This means the complexity of the layer is reduced and obtained without performance loss.